Sectoral exchange rate pass-through in the euro area - Chiara Osbat; Yiqiao Sun; Martin Wagner (European Central Bank (ECB), 2021)
We study exchange rate pass-through (ERPT), i.e., the impact of exchange rate movements on inflation, focusing on euro area import prices at a sectorally disaggregated level. Our estimation strategy is based on VAR-X models, thus incorporating both endogenous and exogenous explanatory variables. The impulse response functions not only allow to study the extent but also the dynamics of ERPT. We find that ERPT is heterogeneous in terms of magnitude across sectors. We further investigate what industry-specific characteristics affect the heterogeneity of ERPT. Across various model specifications including import penetration, market integration, competition and value chain integration, we find that higher market concentration and higher backward integration in global value chains decrease pass-through, in line with previous findings in the literature.
Keywords: C50; F30; F40; 330; exchange rates; import prices; pass-through; euro area; sectoral disaggregation